Perovskite Electronic Ratchets for Energy Harvesting. (10th November 2020) - Hao, Ji; Lu, Haipeng; Nanayakkara, Sanjini U.; Harvey, Steven P.; Blackburn, Jeffrey L.; Ferguson, Andrew J.
Abstract: Electronic ratchets are energy‐harvesting devices that can utilize spatially asymmetric potential distributions to convert nondirectional/random sources of energy into direct current. The potential asymmetry can be generated in a number of ways, but one purported mechanism is to redistribute ions directly within the active material. Utilizing the known propensity for ion migration in lead‐halide perovskites (LHP), the first LHP flashing electronic ratchet is demonstrated by using a voltage stress to intentionally redistribute halide ions within a prototypical 2D perovskite. The resulting asymmetric potential distribution across the 2D perovskite allows for conversion of both electronic noise and unbiased square‐wave potentials into current. Furthermore, simultaneous application of light illumination and voltage stress enhances the asymmetric potential distribution, enabling higher current than the nonilluminated device. This work presents an electronic ratchet system that exploits facile ion migration, which can be modified by both electrical and optical stimuli, providing a model system with the potential to test outstanding mechanistic questions for electronic ratchets. Abstract : The first example of a perovskite‐based electronic ratchet is realized by exploiting the propensity for ion migration in lead‐halide perovskites to create a spatially asymmetric ion distribution in a 2D perovskite field‐effect transistor architecture. The resulting asymmetric potential distribution facilitates conversion of both electronic noise and unbiased square‐wave potentials into direct current.